Understandıng Travel Agencies Attitudes Towards Gastronomy Tourism and Food Tours: The Case of Izmir Turkey - yentür, feray; Demir, Cengiz (International Journal of Contemporary Economics and Administrative Sciences, 2022)
This study considers that travel agencies can be active builders in food tourism destinations. This paper develops and validates a scale to measure the the attitude of travel agencies towards gastronomy tourism and food tours, labeled as support to gastronomy tourism (SGT). Study identified 6 dimensions and 33 initial items through an extensive literature review. Then an exploratory factor analysis was applied to filter the items. The results provided empirical support for a 29-item and six-dimension solution to the SGT scale which consisted of gastronomy tourism knowledge (GTK); approach to gastronomy tourism (AGT); perceived power to impact gastronomy tourism (PPIGT); perceived positive effects of gastronomy tourism (PPEGT); perceived negative effects of gastronomy tourism (PNEGT) and support to gastronomy tourism (SGT) through confirmatory factor analysis. This study contributes to the gastronomy tourism development by revisiting the role of travel agencies. For practical implications, the findings call attention to the importance of provision of knowledge and guidance from authorities as well as the necessity of individual efforts of agency owners to foster the development of gastronomy.